(untitled) (Journal of Laboratory Animal Science, 2021)
An eight-month-old female BALB/c mouse housed and maintained in the Animal Facility of National Brain Research Centre, in accordance with the Committee for Purpose of Control and Supervision of Experiments on Animals (CPCSEA) guidelines, was found to be sick and in distress during the daily health surveillance by a veterinarian. It was found to have delivered four live pups on the previous day. Physical examination of the mouse revealed some membranous mass hanging from the vagina. In addition, there was difficult breathing, distension of the abdomen, head pressing, slightly pale mucus membranes, dehydration and the mouse was minimally responsive to any stimuli. The vulva and vaginal canal were examined for presence of any pups but there were none visible. The abdomen was palpated to confirm presence of pups. After complete clinical examination of the mouse, the condition was diagnosed as ‘dystocia’. Four live pups born on the previous day were fostered with a mother which had delivered on the same day to prevent further pain and suffering to the mouse. A caesarean section was planned on emergency basis to remove foetus from uterus. Post-operatively mouse was maintained on cephalexin and meloxicam daily for five days along with antiseptic dressing of surgical wound with povidone iodine daily for seven days till removal of skin sutures. There was uneventful recovery of mouse ten days after surgery.